ETHNOMATHEMATIC EXPLORATION OF THE GEDHE KAUMAN MOSQUE YOGYAKARTA FROM A GEOMETRIC PERSPECTIVE - Bellinda Bellinda; Dian Meri Afrina; Ratmi Anjani; Lucy Asri Purwasi (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2024)
Ethnomathematics is learning culture-based math learning. The purpose of this research is to explore and find out the mathematical concepts contained in the Gedhe Kauman Mosque Yogyakarta in terms of Geometry. This research uses a qualitative method with an ethnograpic approach. Data collection techniques using observation and documentation techniques. The results of the study show that the Gedhe Kauman Mosque building has ethnomathematics related to mathematical concepts in terms of geometry such as square, rectangle, semiricle, quadrilateral pyramid, and hexagon. The mathematical concepts found in the Gedhe Kauman Mosquecan be utilized to introduce and understand the concept of Geometry through local culture.   Keywords: Exploration, Ethnomathematics, Geometry, Gedhe Kauman Mosque of Yogyakarta